2023
DOI: 10.1017/s1049023x23000493
|View full text |Cite
|
Sign up to set email alerts
|

First-Week Analysis after the Turkey Earthquakes: Demographic and Clinical Outcomes of Victims

Abstract: Background: During a major earthquake, escape attempts or collapsed buildings can result in injury, disability, and even death for victims. The aim of this study is to examine the demographic characteristics, clinical outcomes, and injuries of victims admitted to the emergency department within the first week after an earthquake. Methods: This is a retrospective observational study conducted on earthquake victims who were admitted to the emergency services of a tertiary medical faculty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
(30 reference statements)
0
10
1
Order By: Relevance
“…In research conducted by Sarı et al examining patients admitted to Diyarbakir province during the February 2023 earthquake in Turkey, 4 it was found that extremity traumas were the most common. According to the findings of Bulut et al (2005), 15 the body area that had the highest frequency of injuries was the extremities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In research conducted by Sarı et al examining patients admitted to Diyarbakir province during the February 2023 earthquake in Turkey, 4 it was found that extremity traumas were the most common. According to the findings of Bulut et al (2005), 15 the body area that had the highest frequency of injuries was the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the thoracic and spinal injury rates of the patients are compatible with the literature. 4,16,17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, the recent EQs in Turkey affected 11 neighboring cities including suddenly damaged major logistic centers of the region such as Elazığ, Diyarbakır, Adana, and Hatay. The disasters’ spatial distribution and extreme weather conditions had not been anticipated in TAMP, 11 which caused the action plans to fail and led to unforeseen health needs, especially in the first 3 days after the disaster when there was an increased healthcare demand, 12 and lack of qualified first responders in the affected zones.…”
Section: Utilizing Pacmap In the Aftermath And The Role Of E-health I...mentioning
confidence: 99%
“…Post-earthquake studies mostly include trauma patients in the earthquake zone or patients transferred from the earthquake zone. 69 Studies on the health care utilization of earthquake survivors are limited. To the best of the authors’ knowledge, this is the first study in the literature that evaluates the health care utilization of evacuated victims after the 2023 Turkey earthquake.…”
Section: Introductionmentioning
confidence: 99%